PENGARUH PROGRAM TAHFIDZ AL-QUR’AN TERHADAP PRESTASI BELAJAR SANTRI/YAH PONDOK PESANTREN KH. AHMAD DAHLAN - Zulkarnaen Zulkarnaen; Bustanur Bustanur; Zulhaini Zulhaini (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2020)
The Tahfidz al-Qur'an program is a very noble activity when applied to an educationalinstitution. However, students who take the Tahfidz al-Qur'an program must be willing to leave thelearning process in class like students in general and must be willing to get low marks on generalsubjects because they have to focus on memorizing the Koran, but the problems that the writer foundin boarding schools KH. Ahmad Dahlan is inversely proportional to the statement above, becausemany of the students / yah who follow the special program tahfidz get good grades even though theydo not follow the learning process in class like students / yah in general.This study aims to determine whether there is the effect of the Tahfidz al-Qur'an Program onthe Learning Achievement of Santri / yah Islamic Boarding School KH. Ahmad Dahlan. Thepopulation of this study was 85 students. This research methodology is a type of quantitative research using data collection techniques, namely interviews, documentation and questionnaires.Based on the percentage achieved in this study it can be seen that the coefficient of determination (R Square) of 0.174 or 17.4%. So it can be concluded that the variable Tahfidz Al-Qur'an Program contributes to the Learning Achievement of Santri / well Islamic Boarding School KH. Ahmad Dahlan by 17.4%. While the remaining 82.6%. The data shows that there is an influence of the Tahfidz Al-Qur'an program on the learning achievement of students of the Islamic boarding school KH. Ahmad Dahlan.